2005
DOI: 10.1103/physrevlett.95.177002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Suppressed Screening on the Surface of High TemperatureLa2xSrxCuO4andNd2<

Abstract: Hard X-ray Photoemission spectroscopy (PES) of copper core electronic states, with a probing depth of ∼60Å, is used to show that the Zhang-Rice singlet feature is present in La2CuO4 but is absent in Nd2CuO4. Hole-and electron doping in La2−xSrxCuO4 (LSCO) and Nd2−xCexCuO4 (NCCO) result in new well-screened features which are missing in soft X-ray PES. Impurity Anderson model calculations establish metallic screening as its origin, which is strongly suppressed within 15Å of the surface. Complemented with X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 35 publications
7
44
0
Order By: Relevance
“…The results of the cluster-model calculations did not reproduce the double-peak structures in the experimental main peaks (A and A ′ ). We consider 4 that the double-peak structures in peak A and A ′ stem from the non-local screening effect, since these structures were not seen in the result obtained by soft x-ray [10,[29][30][31][32][33].…”
Section: Intensity [Arbunits]mentioning
confidence: 99%
“…The results of the cluster-model calculations did not reproduce the double-peak structures in the experimental main peaks (A and A ′ ). We consider 4 that the double-peak structures in peak A and A ′ stem from the non-local screening effect, since these structures were not seen in the result obtained by soft x-ray [10,[29][30][31][32][33].…”
Section: Intensity [Arbunits]mentioning
confidence: 99%
“…Then, higher E K hard x-ray PES named HAXPES is understood to be more favorable for probing bulk electronic structures of SCES. 5,6 However, the photoionization cross sections become orders of magnitude decreased with increasing h from 1 to 8-10 keV. 7 In spite of the higher possible h resolution, the resulting total resolution of HAXPES is often spoiled by the single nucleus recoil effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that the spectral feature in the 'Bulk' is drastically different from that at the 'Surface'. The structure at 931-932 eV in figure 1(b) corresponds to the feature induced by the non-local screening effect reported by hard x-ray PES [21] for the core-hole excitation. Thus, the 'Bulk' components are confirmed to be dominant in our high-hν near-normal emission PES spectra with a kinetic energy of around 500 eV.…”
Section: Methodsmentioning
confidence: 56%
“…For quasi-two-dimensional electron systems such as HTSCs, it has long been thought that the electronic structures of the top (or surface) conducting layer are equivalent to those of the bulk layers, which are responsible for the superconductivity. High-hν core-level PES studies [21]- [26], however, recently suggested that the electronic structures of the bulk CuO 2 layers, in particular for optimally doped Nd 1.85 Ce 0.15 CuO 4 , are noticeably different from those of the surface CuO 2 layer, which are mainly detected by low-hν ARPES [6,8,22]. High-hν ARPES [23,24] is therefore essential for directly revealing the bulk QD.…”
Section: Introductionmentioning
confidence: 99%